For Better or for Worse: A Look Into Neutrophils in Traumatic Spinal Cord Injury - Zivkovic, Sandra; Ayazi, Maryam; Hammel, Grace; Ren, Yi (Frontiers in Cellular Neuroscience, 2021)
Neutrophils are short lived cells of the innate immune system and the first line of defense at the site of an infection and tissue injury. Pattern recognition receptors (PRRs) on neutrophils recognize pathogen associated molecular patterns (PAMPs) or danger associated molecular patterns (DAMPs), which recruit them to the destined site. Neutrophils are professional phagocytes with efficient granular constituents that aid in the neutralization of pathogens. In addition to phagocytosis and degranulation, neutrophils are proficient in creating extracellular traps (NETs) which immobilize pathogens to prevent their spread. The role of neutrophils in infection is well studied; however, there is less emphasis placed on the role of neutrophils in tissue injury, such as traumatic spinal cord injury (SCI). SCI is a devastating condition with temporary or permanent paralysis in injured patients. Upon the initial mechanical injury, innate immune system is activated in response to the cytokines produced by the resident cells of the injured spinal cord initiating the inflammatory cascade. This review provides an overview of the essential role of neutrophils in inflammation and explores the contribution of neutrophils to the pathologic changes in the injured spinal cord.